Correction: High-efficiency, anode-free lithium–metal batteries with a close-packed homogeneous lithium morphology. Issue 4 (16th March 2022) - Su, Laisuo; Charalambous, Harry; Cui, Zehao; Manthiram, Arumugam
Abstract : Correction for 'High-efficiency, anode-free lithium–metal batteries with a close-packed homogeneous lithium morphology' by Laisuo Su et al., Energy Environ. Sci., 2022, 15, 843–854, DOI: ; 10.1039/D1EE03103A .